Interaktif Virtual Tur Melalui Media Elektronik: Kualitas Pelayanan, Kepuasan Wisatawan, Word of Mouth dan Niat Untuk Berkunjung Kembali - Ni Wayan Marsha Satyarini (UNIVED Press, 2022)
Starting with a walking tour which has the concept of traveling by walking around a destination to get to know the other side of the story which tourists rarely know, from museums, culinary delights, and other historical places. In early 2020, coronavirus hit the world. Indonesia implemented large-scale social restrictions (PSBB) that were imposed over the past few months, bringing tourism to a halt. On this situation, many walking tour organizers and tour guides use the latest innovation, namely interactive virtual tours. The purpose of this study is to investigate the role played by tour guides and service providers or interactive virtual tour organizers in providing services electronically which have an influence on the level of tourist satisfaction which is ultimately transmitted by word of mouth electronically and in the end they want for a revisit intention as visit in person. This study used a quantitative method with 210 respondents. The study used a Structural Equation Modeling (SEM) model using AMOS version 23.0 software.